FAKTOR-FAKTOR PENENTU STRUKTUR MODAL OPTIMAL PERUSAHAAN SUBSEKTOR GAS, OIL, AND COAL - TOMMY HARLIE; BENY (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study aims to examine the influence of internal aspects on capital structure in companies within the gas, oil, and coal subsectors listed on the Indonesia Stock Exchange during the 2017–2023 period. The independent variables in this study include Profitability, Growth Opportunity, Tangibility, Corporate Tax, and Tax Shield. The research sample was determined using purposive sampling, resulting in a total of 119 observations from 17 companies. The data were analyzed using statistical methods to identify the relationships among these variables. The results showed that Growth Opportunity and Tangibility significantly influence capital structure, reflecting the importance of growth opportunities and tangible assets in corporate financing decisions. In contrast, Profitability, Corporate Tax, and Tax Shield did not have a significant effect on capital structure. These findings imply that companies should prioritize growth opportunities and optimize tangible assets in making financing decisions, while investors may consider these factors when evaluating firms’ capital structure and financial strategies.